2006
DOI: 10.1007/bf02959274
|View full text |Cite
|
Sign up to set email alerts
|

Effects of limited feeding of aflatoxin B1 contaminated feed on the performance of broilers

Abstract: The forty-two days long experiment was conducted on a total of 1000 Arbor Acres broilers, divided into two groups. Both groups of broilers were fed with a commercial feed mixture which consisted of standard feedstuffs and contained enough nutrients regarding the requirements. During the first three weeks of the trial, corn naturally contaminated with AFB1 0.0445 ppm per kg dry matter was used in the amount of 20% in the experimental group, while AFB1 free corn was given to birds in the control group. After the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 11 publications
2
7
0
Order By: Relevance
“…Similarly, previous study reported that BW on d 21 was decreased by low levels of AFB 1 and AFB 2 (16 to 82 μg/kg AFB 1 and 3 to 14 μg/kg AFB 2 ) in broilers fed contaminated diets and the reduction increased with an increasing of naturally contaminated corn [4]. The increased F/G in broilers fed AFB-contaminated diets (44.5 μg/kg) was observed by previous studies [26]. Others also observed negative effects of AFB (1 to 5 mg/kg) on growth performance in broilers [5][6][7]27].…”
Section: Growth Performancesupporting
confidence: 80%
“…Similarly, previous study reported that BW on d 21 was decreased by low levels of AFB 1 and AFB 2 (16 to 82 μg/kg AFB 1 and 3 to 14 μg/kg AFB 2 ) in broilers fed contaminated diets and the reduction increased with an increasing of naturally contaminated corn [4]. The increased F/G in broilers fed AFB-contaminated diets (44.5 μg/kg) was observed by previous studies [26]. Others also observed negative effects of AFB (1 to 5 mg/kg) on growth performance in broilers [5][6][7]27].…”
Section: Growth Performancesupporting
confidence: 80%
“…It has been suggested that clinical, hematological-biochemical, and histopathological changes occur in broilers fed 50-200 µg/kg of dietary AFB 1 (Whitlow andHagler 2005, Resanovic andSinovec 2006). The observed differences in response to chronic aflatoxicosis are probably due to differences in AFB 1 sensitivity of the particular bird population assayed in each experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, food and feeds have been seriously contaminated with mycotoxins among which aflatoxin, zearalenone, fumonisin, deoxynivalenol, and ochratoxin are the most commonly found (Qu et al 2017). Furthermore, food and feeds are frequently co-contaminated with two or more mycotoxins, and their interactions may exert additive or synergistic effects (Resanovic and Sinovec 2006). The consumption of mycotoxin-contaminated food and feeds leads to reduced nutrient absorption (Verma et al 2004), poor performance, immunosuppression (Richard 2007), residues in animal products (Qu et al 2017), and increased susceptibility to infectious and parasitic diseases (Ma et al 2015), and cause serious reproductive problems leading to economic losses in the poultry industry (Wade et al 2017), resulting in a massive economic impact worldwide on human health, animal health, and agricultural trade.…”
Section: Introductionmentioning
confidence: 99%
“…This inconsistency in FCR was also observed in broilers. FCR was decreased in broilers fed naturally contaminated AFB 1 diets (44.5 μg/kg) [ 25 ], whereas FCR was improved by purified AFB 1 (1,500 μg/kg) [ 26 ]. This inconsistence may be due to AFB 1 origins (corn naturally contaminated or inoculated with purified mycotoxins), dosage and species-specificity.…”
Section: Discussionmentioning
confidence: 99%